Characterization of the Geranylgeranyl Diphosphate Synthase Gene in Acyrthosiphon pisum (Hemiptera: Aphididae) and Its Association With Carotenoid Biosynthesis - Ding, Bi-Yue; Niu, Jinzhi; Shang, Feng; Yang, Li; Chang, Teng-Yu; Wang, Jin-Jun (Frontiers in Physiology, 2019)
Carotenoids play many crucial roles in organisms. Recently, the de novo synthesis of carotenoids has been reported in pea aphid (Acyrthosiphon pisum) through horizontally transferred genes. However, their upstream pathway in the pea aphid is poorly understood. Geranylgeranyl diphosphate synthase (GGPPS) is the functional enzyme in the synthesis of geranylgeranyl diphosphate (GGPP) which is a precursor for the biosynthesis of many biological metabolites, including carotenoid synthesis. In this study, we performed a series of experiments to characterize GGPPS gene and its association with carotenoid biosynthesis. 1) determining the transcript abundance and carotenoid content in two geographical strain with red and green morphs, and 2) examining the abundance of carotenoid related genes and carotenoid levels after silencing of GGPPS in both red and green morphs. We observed that GGPPS was more highly expressed in the green morph than in the red morph of two strains of the pea aphid. The total level of carotenoids was also higher in green morphs than in red morphs in both strains. In addition to the total carotenoid difference, the carotenoids found in the two morphs also differed. There were α-carotene, β-carotene, and γ-carotene in the green morphs, but three additional carotenoids, including cis-torulene*, trans-torulene*, and 3,4-didehydrolycopene*, were present in the red morphs. Silencing the GGPPS by RNAi in both the red and green morphs decreased the expression of some carotenoid biosynthesis-related genes, including carotenoid synthase/cyclase genes and carotenoid desaturase genes in green morphs. Carotenoid levels were decreased in both green and red morphs. However, the specific carotenoids present were not changed after silencing GGPPS. These results demonstrated that GGPPS may act as the upstream enzyme to influence the synthesis of the total amount of carotenoids. The present study provided important molecular evidence for the conserved roles of GGPPS associated with carotenoids biosynthesis and will enhance further investigation on the mechanisms of carotenoid biosynthesis in pea aphid.